THE PHYSICOCHEMICAL PROPERTIES OF EDIBLE PROTEIN FILMS - Seda Ogur (Chiriotti Editori, 2015)
In the present study, edible films from isolated or concentrated protein sources and from proteins of two different fish species were produced. The texture properties, light transmission (LT) and oxygen permeability (OP) of producing films were determined. The CL film settled in the second range according to both tension test parameters, thus outclassing the other tested films. The WG film possessed the lowest LT, so making it more effective in protecting of food products from light than the other tested films. The SPI film with the lowest OP value can be used for the purpose of protecting of food products from harmful effects of oxidation.